The positive aspects of the decriminalization of gambling in Brazil (Research, Society and Development, 2022)
The present work sought to study the social improvements resulting from the legalization of gambling and the best way to regulate the practice of this activity. A historical synthesis of the games was demonstrated and how society is quite adept at them, in addition to analyzing the positive aspects of their legalization and discussing the most effective way to regulate this lucrative market, considering that the collection of taxes will only affect the practitioners, and as in other countries, gambling would be seen as a source of social capital and not as something derogatory and there is still the possibility of bringing a great economic return to society. For this, the methodology of systematic literature review was used, focusing on the decriminalization and subsequent regulation of gambling, with this, it is concluded that the decriminalization of gambling will bring numerous economic and social benefits to society.